INTEGRATED MANAGEMENT AND THE USE OF EMERGING TECHNOLOGIES IN PUBLIC SCHOOLS IN MANAUS - Gomes Viana, Jomariaze (Revista Gênero e Interdisciplinaridade, 2024)
Integrated management and the use of emerging technologies have become fundamental for the advancement of education in public schools. In Manaus, the implementation of these practices still faces significant challenges, but also represents a great opportunity to transform local education. This article discusses the importance of integrated management, the application of emerging technologies in Manaus public schools and the challenges faced in the implementation process. From a literature review, we seek to understand how these tools can improve teaching and learning, promoting a more inclusive and efficient education, analyzing the impact of integrated management combined with the use of emerging technologies in the context of public schools in Manaus